Alcances del principio de causalidad en el impuesto a la renta empresarial - Durán Rojo, Luis (2009)
The following article presents the implications about the practice of the causality principle for the determination of the income set with intention to apply the business income tax.We start considering the fact that this tax can be imposed to acquire goods known as a deductible expense of the practice, but not from those that are going to be part of the compatible cost to expropriate. Then, we make an extensive analysis about the way the Peruvian income tax law has configured the approaches of this principle and the understanding emerged from important jurisprudence cases from the members that solve problems, specially the Tax Court, when adopting a fast principle of expenses without causes.At the same time, this article describes the achievements of the rational and normality cost principles, so important for the evaluation of the performance of the principle of causality.Finally, we present some ideas about the accreditation of the cost facing and its relation to the causality principle.